The Effectiveness Of The Hope Family Program As Poverty Reduction Effort (Case Study In Pringsewu District, Lampung Province) - Rohmi, Misfi Laili (Jurnal Mamangan, 2022)
The problem of poverty is still an important issue in Indonesia. The Indonesian government has made various efforts to tackle the problem of poverty, one of which is through the Family Hope Program (PKH), which is a cluster of policies based on social assistance and protection in the form of meeting the basic needs of health and education for poor individuals and households . The hope is that with quality health and education, it will break the chain of poverty. In its implementation, PKH does not escape various problems , starting from the input aspect to the output aspect . Thus, this study aims to see the effectiveness of PKH in terms of program input, process, and output aspects. This research is a type of quantitative descriptive research with a questionnaire instrument guided by the researcher. The data analysis technique uses a scoring questionnaire which is then compared with the ideal criteria that have been set in PKH. m The results showed that PKH was effective from the input aspect , process aspect and output aspect in the education sector . However, PKH has not been effective in terms of output in the health sector on several indicators. In addition, PKH has implications for the economic aspect in the form of increasing labor productivity through improving the quality of human resources by increasing the percentage of students who continue to junior high and high school levels. During the 6 (year) program, there was an increase in education participation from SD to SMP by 20% and participation from SMP to SMA levels by 19%.